C-Reactive Protein Levels in the Brugada Syndrome. (29th November 2011) - Bonny, Aimé; Tonet, Joelci; Márquez, Manlio F.; De Sisti, Antonio; Temfemo, Abdou; Himbert, Caroline; Gueffaf, Fatima; Larrazet, Fabrice; Ditah, Ivo; Frank, Robert; Hidden-Lucet, Françoise; Fontaine, Guy
Abstract : Background . Inflammation in the Brugada syndrome (BrS) and its clinical implication have been little studied. Aims . To assess the level of inflammation in BrS patients. Methods . All studied BrS patients underwent blood samples drawn for C-reactive protein (CRP) levels at admission, prior to any invasive intervention. Patients with a previous ICD placement were controlled to exclude those with a recent (<14 days) shock. We divided subjects into symptomatic (syncope or aborted sudden death) and asymptomatic groups. In a multivariable analysis, we adjusted for significant variables (age, CRP ≥ 2 mg/L). Results . Fifty-four subjects were studied (mean age 45 ± 13 years, 49 (91%) male). Twenty (37%) were symptomatic. Baseline characteristics were similar in both groups. Mean CRP level was 1, 4 ± 0, 9 mg/L in asymptomatic and 2, 4 ± 1, 4 mg/L in symptomatic groups ( P = .003). In the multivariate model, CRP concentrations ≥ 2 mg/L remained an independent marker for being symptomatic ( P = .018; 95% CI: 1.3 to 19.3). Conclusion . Inflammation seems to be more active in symptomatic BrS. C-reactive protein concentrations ≥ 2 mg/L might be associated with the previous symptoms in BrS. The value of inflammation as a risk factor of arrhythmic events in BrS needs to be studied.